Analisis Tegangan Balik Terhadap Sistem Kerja Wesel Elektrik Tunggal Di Stasiun Jakarta Kota - Sri Hartanto; Alif Akbar Rizqullah; Abdul Kodir Albahar (Teknik Elektro Universtias Krisnadwipayana, 2025)
Electric switches are vital components in railway signaling systems, responsible for directing train tracks. At Jakartakota Station, single electric switches are prone to disturbances caused by high reverse voltage, which can blow 4 A fuses and halt operations. Based on this issue, this study analyzes the effect of using a 10 Ohm 100Watt resistor as a reverse voltage suppression solution. The title was chosen to reflect the specific component specifications, the type of switch system studied, and the precise research location, ensuring a clear research focus. The methodology included measuring current and voltage before and after resistor installation, analyzing system performance under both normal and obstructed conditions, and evaluating effectiveness without major modifications to indoor systems. The results show that installing the resistor reduced detection current from 4.1 A to 1.9 A, preventing fuse failures. Detection voltage remained within the relay’s operating range, while power voltage was unaffected. Compared to previous studies, the novelty of this research lies in its direct testing within an active operational environment, the use of resistor specifications tailored for high-current loads and outdoor conditions, and a practical approach that can be implemented without overhauling the entire system design. Thus, the use of a 10 Ohm 100Watt resistor is proven effective in enhancing the stability and reliability of electric switch systems, extending component lifespan, and supporting operational safety in Indonesia’s railway sector.